VIRAL HEPATITIS A DISEASE.EPIDIMIOLOGY.CLINICAL COURSE.TREATMENT AND PREVENTION (Лучшие интеллектуальные исследования, 2025)
Abstract: Viral Hepatitis A disease is one of the infectious diseases that damage the liver in the human body. It develops under the influence of the hepatitis A virus (HAV) and is transmitted mainly through food or through contaminated water and food products. Viral hepatitis A is widespread around the world, being more common, especially in areas with insufficient hygiene conditions. Research in the field of Epidemiology, clinical course, methods of treatment and Prevention of the disease helps to develop its prevention and effective treatment measures.